(untitled) (Conferencea, 2022)
Firebrick plays an important role in many industrial enterprises, including the production of aluminum, cement, glass, iron, oil and steel. Refractory bricks differ in composition depending on their use. The main types are made from raw materials such as aluminum, carbon chrome ore, dolomite, magnesite, silicon and zircon. In the production of refractory bricks, it is necessary to take into account the granulometric composition, as a result of which they become a dense and durable product. Sito-burat SM-237A sorting machine is currently in use. The main feature of the used sorting machine is that it requires the separation of raw materials into the required fractions. The main problem of the raw material sorting machine is the uneven distribution of fractions.